A Truly Ancient "Great Divergence"––A New History of the Chinese State. Issue 1 (2nd January 2019) - Goldstone, Jack A.
Abstract: Zhao provides a new view of why China remained politically united, but unable to achieve industrialization. He traces the roots of both conditions back to the Warring States period, when Chinese leaders developed authoritarian-bureaucratic governance and combined it with Confucian moral ideas and statecraft as a legitimating ideology. This Confucian-legalist state structure proved resilient enough to hold China together despite changes of dynasty, foreign invasions, the incursion of Buddhism, and heterodox ideas. Zhao argues that this stable state structure also precluded industrialization, because it marginalized commercial thinking and allowed no space for autonomous merchant organizations or other corporate or privileged bodies. This is a valuable and impressive overview of Chinese history; but European and Chinese histories themselves need to be viewed as embedded in global history. In this context, Europeans' awareness of their technical backwardness compared to China, and differences in the evolution of classical thought in Europe vs. the evolution of Confucianism in China, are also necessary to explain why Europe was able to industrialize but China was not.